Experimental Use of Self Test Endoscopy for Cervical Cancer Screening - Munafiah, Durrotun; Fatoni, Muhammad Hilman; Mayangsari, Dewi; Widyawati, Melyana Nurul; Sardjono, Tri Arief (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Cervical cancer is the fourth deadly cancer that attack women worldwide. Regardless of age, cancer attack all age range, from children to elderly. Cancer prevalence in Indonesia reaches 1.4 per 1000 population. For cervical canser case, Semarang was one of city in the Province of Central Java which have highest cervical cancer case in 2011. Cases of cervical cancer in Semarang increased from 2,782 in 2010 to 5,155 in 2011. By comparison around the world, Indonesia ranked seventh in the world and the first in Asia. The handling of cancer in Indonesia faces various obstacles that cause nearly 70% of patients found in an advanced stage. Implementation of technology could minimize that condition. In cervical cancer cases, the use of cervical screening program could decrease incidences of cervical cancer. By using cervical screening program, early detection of cervical cancer could be done. Self-test endoscopy is one of the method to detect cervical cancer early. This paper elaborate how self-test endoscopy is used to screen cervical cancer. By using self-test endoscopy, one of seven subject in this experiment detected as cervical cancer subject. Keywords: Cervical cancer screening; Self-test endoscopy